What are the key drivers to promote continuance intention of undergraduates in online learning? A multi-perspective framework - Zhang, Jintao; Zhang, Mingbo; Liu, Yanming; Zhang, Liqin (Frontiers in Psychology, 2023)
The purpose of this study is to investigate the key predictors of online learning system continuance intention using expectation-confirmation theory and information system success model as the theoretical framework. A total of 537 respondents participated in the questionnaire to measure their self-reported responses to eight constructs (perceived usefulness, interaction, confirmation, satisfaction, continuance intention, information quality, system quality, service quality). Convenience sampling was used to obtain participants in this study. Partial least square structural equation model is used for data analysis. The results showed that all the hypotheses were validated except that there was no significant positive relationship between online learning interaction and student satisfaction. Meanwhile, the variance of the continuance intention of the online learning system reached 74.0%, falling within the moderate to substantial. In addition, the multi-group analysis of perceived usefulness, satisfaction and continuance intention showed that there was no significant gender difference in the above two relationships. Finally, this study also puts forward the theoretical and practical implications of college students' continuance intention of online learning system.